The molecular-genetic and phylogenetic analysis of the hemaglutinin gene from influenza viruses - Smutko, O.Yu.; Radchenko, L.V.; Fesenko, A.Yu.; Holubka, O.S.; Budzanivska, I.G.; Mironenko, A.P. (Вiopolymers and Cell, 2018)
Aim. To perform a phylogenetic and molecular-genetic analysis of the HA genes of influenza viruses that circulated in Ukraine during the 2016–2017 epidemic season, and to compare them with those that circulated in the world. Methods. Samples (nasopharyngeal swabs from patients) were analyzed using the real-time polymerase chain reaction (RT-PCR). Phylogenetic trees were constructed using MEGA 7 software. 3D structures were constructed in Chimera 1.11.2rc software. Results. Ukrainian isolates from the 2016–2017 season have substitutions in the antigenic sites which were not detected earlier; they and can influence the antigenic properties of viruses. Otherwise the A(H3N2) and B/Victoria viruses retained the similarity to the vaccine strains. For the A(H1N1)pdm09, a higher similarity to the vaccine strain recommended for the 2017–2018 epidemic season was observed. Conclusions. In the 2016–2017 epidemic season, all influenza viruses –A(H3N2), A(H1N1)pdm09 and B/Victoria acquired a number of unique amino-acid substitutions in the HA gene. The results of this study reaffirm the continuous genetic variability of circulating seasonal influenza viruses and the need for continued systematic antigenic and molecular surveillance. Мета. провести філогенетичний та молекулярно-генетичний аналіз генів НА вірусів грипу, що циркулювали на території України протягом епідемічного сезону 2016–2017 років та порівняти їх з тими, що циркулювали в світі. Методи. Зразки (назофаригіальні змиви від паціентів) були проаналізовані методом полімеразної ланцюгової реакції в реальному часі (ЗТ-ПЛР). Філогенетичні дерева будували в програмі MEGA7. 3D структури будували в програмі Chimera 1.11.2rc. Результати. Українські ізоляти мали заміни в антигенних сайтах, що виникли в попердніх сезонах та епідемічному сезоні 2016–2017 років і не виявлялись раніше, які можуть мати вплив на антигенні властивості вірусу. Не дивлячись на це, віруси грипу A(H3N2) та B/Victoria зберегли подібність до вакцинних штамів. Для вірусів грипу A(H1N1)pdm09 була показана вища подібність до вакцинного штаму, рекомендованого на епідемічний сезон 2017–2018 років. Висновки. В епідемічному сезоні 2016-2017 років всі віруси грипу – A(H3N2), A(H1N1)pdm09 та B/Victoria набули значну кількість унікальних амінокислотних заміщень в гені гемаглютиніну. Результати цього дослідження підтверджують постійну генетичну мінливість циркулюючих вірусів сезонного грипу та необхідність постійного систематичного антигенного та молекулярного нагляду. Цель. Провести филогенетический и молекулярно-генетический анализ генов НА вирусов грипа, которые циркулировали на территории Украины в эпидемическом сезоне 2016–2017 годов и сравнить их с теми, что циркулировали в мире. Методы. Образцы (назофаригиальные смывы от пациентов) были проанализированы методом полимеразной цепной реакции в реальном времени (ОТ-ПЦР). Филогенетические деревья строили в программе MEGA7. 3D структуры строили в программе Chimera 1.11.2rc. Результаты. Украинские изоляты имели замены в антигенных сайтах, возникшие в предыдущих сезонах и эпидемическом сезоне 2016–2017 годов и не выявлялись ранее, которые могут повлиять на антигенные свойства вируса. Несмотря на это, вирусы гриппа A (H3N2) и B / Victoria сохранили сходство с вакцинными штаммами. Для вирусов гриппа A (H1N1) pdm09 было показано сходство с вакцинным штаммом, рекомендованным на эпидемический сезон 2017–2018 годов. Выводы. В эпидемическом сезоне 2016–2017 годов все вирусы гриппа –A(H3N2), A(H1N1)pdm09 и B/Victoria приобрели значительное количество уникальных аминокислотных замещений в гене гемагглютинина. Результаты этого исследования подтверждают постоянную генетическую изменчивость циркулирующих вирусов сезонного гриппа и необходимость постоянного систематического антигенного и молекулярного надзора.